Audit committees, political connections, and audit quality on tax avoidance - Nurlita Sukma Alfandia; Pebrika Ayunda Putri (Junal Ilmu Manajemen, 2023)
Differences in the results of previous studies regarding the relationship between audit committees, political connections, and audit quality on tax avoidance make this research necessary. This study aims to thoroughly review and identify empirical evidence about the impact of audit committees, political ties, and audit quality on tax avoidance. Tax avoidance is a dependent variable. Audit quality, audit committees, and political connections are independent variables. Political connections were calculated using the number of Board of Commissioners with the formula of calculating the number of Commissioners: The Board of Commissioners was politically connected. The audit committee was calculated using the number of members of the company's audit committee. The audit quality measurement in this study is dummy variables. This study is explanatory research and uses a quantitative methodology. The 36 samples included in this study are mining firms listed between 2017 and 2019 on the Indonesia Stock Exchange. Purposive sampling was used to collect samples, while multiple linear regression was the technical data analysis method used in this study. When selecting how to disclose financial information, the corporation considers the audit committee. Political connections negatively affect tax avoidance. It reveals how political ties to the board of commissioners also affect tax evasion. Audit quality has a detrimental effect on tax evasion as well. The Big Four Public Accounting Firm's (KAP) audit standard ensures accurate financial data.